2005
DOI: 10.1291/hypres.28.431
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Enhances the Cardioprotective Effect of an Angiotensin-II Receptor Blocker in an Experimental Animal Model of Heart Failure

Abstract: This study was designed to examine the hypothesis that a calcium channel blocker nifedipine (CCB) could enhance the cardioprotective effect of an angiotensin-II receptor blocker candesartan (ARB) in the treatment for heart failure. Isoproterenol (ISP) was injected into male rats at 300 mg/kg to produce progressive heart failure. Three months later, the rats were divided into 4 groups and treated for 4 weeks with 1) vehicle (n =20), 2) ARB at 0.2 mg/kg/day (n =6), 3) CCB at 10 mg/kg/day (n =6), or 4) both drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…27,48 In the present study, the plasma LPO level, a marker of systemic oxidative stress, was significantly increased in mice exposed to intermittent hypoxia. In addition, intermittent hypoxia significantly enhanced NADPH-dependent superoxide production and 4-HNE expression in the LV myocardium.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…27,48 In the present study, the plasma LPO level, a marker of systemic oxidative stress, was significantly increased in mice exposed to intermittent hypoxia. In addition, intermittent hypoxia significantly enhanced NADPH-dependent superoxide production and 4-HNE expression in the LV myocardium.…”
supporting
confidence: 54%
“…23 The percentage area of 4-HNE and Ang II staining was measured by the method reported previously. 27 …”
Section: Immunohistochemistry For 4-hydroxy-2-nonenal and Ang IImentioning
confidence: 99%
“…Both intensity and area were analyzed by the method published previously. 17 The data from all the examined sections were used to calculate the % area of positive pixels relative to the total examined area in pixels.…”
Section: Immunohistochemistry For Hif-1 and Vegfmentioning
confidence: 99%
“…9) Hayashi, et al 10) also reported that a combination of ARB and nifedipine enhances this effect, and increases the myocardial capillary density. On the other hand, Komuro, et al 11) suggested that long-acting Ca antagonists may prevent cardiac hypertrophy by altering calcineurin activation due to Ca 2+ inflow into the myocardium during the onset and progression of cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 94%